Cochrane Database of Systematic Reviews 2004
DOI: 10.1002/14651858.cd004768
|View full text |Cite
|
Sign up to set email alerts
|

Single dose oral diclofenac for acute postoperative pain in adults

Abstract: Oral diclofenac is an effective single-dose treatment for moderate to severe postoperative pain. There was no significant difference between diclofenac and placebo in the incidence of adverse effects, or between diclofenac sodium and potassium, different pain models, smaller and larger trials and trials of higher and lower quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…The area under the curve (AUC) is a measure that is often used in clinical pharmacology, but it can also be used for clinical endpoints—for example, the use in pain assessment. 10 11 12 13 A higher AUC represents a higher satisfaction with pain relief. The AUC was calculated for the duration of labour and for the time that pain relief was administered.…”
Section: Methodsmentioning
confidence: 99%
“…The area under the curve (AUC) is a measure that is often used in clinical pharmacology, but it can also be used for clinical endpoints—for example, the use in pain assessment. 10 11 12 13 A higher AUC represents a higher satisfaction with pain relief. The AUC was calculated for the duration of labour and for the time that pain relief was administered.…”
Section: Methodsmentioning
confidence: 99%
“…The non-selective non-steroidal anti-inflammatory drug (NSAID) diclofenac sodium has long been used to treat acute pain and inflammation [1], and is effective in various acute forms of pain [2]. Due to its poor solubility, the parenteral formulation of diclofenac sodium (Voltarol Ò ampoules) currently available in Europe contains the solvents propylene glycol and benzyl alcohol [3] that allows intramuscular and intravenous administration; intravenous Voltarol Ò requires reconstitution, dilution, buffering and slow infusion over C30 min [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Randomized controlled trials and their meta-analyses have shown that the use of celecoxib for all surgical procedures reduces pain scores and opioid consumption, expedites return of bowel function, return to normal daily activities and improves patients satisfaction1 4,15 . The COX-2 selective inhibitors have similar efficacy in the reduction of postoperative nausea and vomiting due to omission or opioid-sparing effects as nonselective NSAIDs, but they are superior in reducing other opioid adverse events 16 . The gastric ulceration rate was similar to placebo and significantly lower than nonselective NSAIDs in high-risk patients, even for short-term use 17 .…”
Section: Non-steroidal Anti-inflammatory Drugs (Nsaids) and Cyclooxyg...mentioning
confidence: 99%